Studying the physicochemical regularities in the color- and phase formation processes of clinker ceramic materials - Fedorenko, Olena; Prysiazhna, Larysa; Petrov, Serhii; Chyrkina, Maryna; Borysenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2018)
The paper reports results of a comprehensive study, aimed at developing formulation-technological parameters for obtaining volumetrically dyed clinker ceramic materials with a wide range of colors. A possibility has been proven to obtain a ceramic clinker when using the polymineral clay raw materials at a temperature of 1,100 °C. The expediency has been shown to replace expensive ceramic pigments in the composition of masses with anthropogenic materials containing the oxides of metals with variable valency: wastes from alkaline earth syenite extraction, pegmatite enrichment, and production of ferrotitanium alloys. This shows possibilities for reducing the production cost of clinker ceramic articles. The influence of the formulation of raw materials compositions on the processes of color- and phase-formation of ceramic clinker has been investigated, depending on the character of furnace atmosphere. It was established that the brown coloration of clinker ceramics under conditions of oxidative annealing is predetermined by the presence of phases of hematite α-Fe2O3 and Mn2O3. At annealing in a reducing medium, products acquire color in the range from dark brown to black at the expense of formation of magnetite Fe3O4 and gaussmanite Mn3O4. The products’ terracotta color is due to the presence of phases of hematite and hedenbergitis CaFeSi2O6. The condition for obtaining clinker ceramics of yellow color is to limit the formulation’s content of Fe2O3 to 3 % by weight, as well as the presence of the SiO2 rutile phase. The paper illustrates the effect of the overall content of oxides of metals with a variable valence S(Fe2O3+FeO+MnO+Mn3O4) on the coloration characteristics of clinker ceramics. The ratios have been derived between the phase-forming oxides Fe2O3/(Al2O3+CaO), (Fe2O3+Mn2O3)/(FeO+Mn3O4) and TiO2/(Al2O3+CaO), as well as the limits in their variation, providing for the formation of color-carrying phases responsible for obtaining products of the desired color under conditions of oxidative and reductive annealing